Genetic variation in quantitative traits of black gram (Vigna mungo (L.) Hepper) induced by gamma rays treatment in M3 generation - S. Velu, D. Arulbalachandran, L. Mullainathan (Journal of Phytology, 2009)
Black gram is an important pulse crop occupying unique position in Indian agriculture. The major constraints in achieving higher yield of black gram are absence of suitable ideotypes for different cropping systems, poor harvest index and susceptibility to diseases. Research on this species is lagging behind than that of cereals and other legumes. In order to improve yield and other polygenic characters, mutation breeding can be effectively utilized. However, Mutation induction has become an establishment tool in plant breeding to supplement existing germplasm and to improve cultivars in certain specific traits. In the present investigation, the attempt was made to improve some of the quantitative traits of black gram by using gamma ray irradiation. The study revealed that gamma irradiation induces and enhance the quantitative traits at 60 kR that evident to improving of black gram with genetic variation.